Pengembangan Media Audio Visual Berbasis Budaya Lokal Sipakatau Dalam Pembelajaran IPS Pada Peserta Didik SD Se Gugus SDN 57 Campaga Kabupaten Bantaeng - Wahyuni, Sri (Phinisi Integration Review, 2018)
This study aims to (1) find out the description of the needs of the development of audio-visual media based on sipakatau local culture in social science learning, (2) to know the description of the design of the development of audio-visual media based on sipakatau local culture in social science learning, and (3) to know the level of validity, effectiveness of audio-visual media based on sipakatau local culture in social science learning. The research method used is Research and Development. The steps of this research is the formulation of learning objectives by first doing the mapping of Core Competencies, Basic Competencies, and Indicators of Competence Achievement, furthermore development of learning materials, script writing, narrative writing, sound recording, internal design testing, and product manufacture. The result of needs analysis of audio visual media development based on sipakatau local culture sipakatau is needed, because it can motivate students to actively participate in social science learning become fun for the achievement of learning objectives. Also at the same time as a means of fostering the character of students in order to live in mutual respect and respect for humanity. Validation results indicate that the learning media products and their instruments are expressed in very valid categories. The teacher's response as a media user states that the learning media is in a very practical category. The effectiveness of the use of instructional media is evidenced by student activity observation in social science learning and student learning result test. The result of observation found that the average of student activity is in very good category. The test of learning results shows that the mean score after learning is greater than the average score before the learning.